2011
DOI: 10.1111/j.1349-7006.2011.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Monocarboxylate transporters 1 and 4 are involved in the invasion activity of human lung cancer cells

Abstract: Cancer cells show constitutive upregulation of glycolysis, and the concentration of lactate thus produced correlates with prognosis. Here, we examined whether lactate concentration and lactate transporter expression are related to migration and invasion activity. We found that the expression of the monocarboxylate transporters MCT1 and MCT4, but not MCT5, in human lung cancer cell lines was significantly correlated with invasiveness. To clarify the effects of MCT1 and MCT4 expression on invasion, we performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 32 publications
5
141
1
3
Order By: Relevance
“…While the migration of glucose-starved TCs depends on MCT1 expression and activity (Figure 6), CD147 is known to promote invasion, 15,36,37 so it can logically be proposed that MCT1-CD147 accumulation allows cell to escape from harsh environments. Accordingly, forced overexpression of either of the partners (resulting in the stabilization of both of them as previously reported in other systems) [13][14][15] was sufficient to promote TC migration (Figure 6f and Supplementary Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the migration of glucose-starved TCs depends on MCT1 expression and activity (Figure 6), CD147 is known to promote invasion, 15,36,37 so it can logically be proposed that MCT1-CD147 accumulation allows cell to escape from harsh environments. Accordingly, forced overexpression of either of the partners (resulting in the stabilization of both of them as previously reported in other systems) [13][14][15] was sufficient to promote TC migration (Figure 6f and Supplementary Figure 6C).…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of MCT1 to migration was seen with glucose or serum as chemoattractants but not with lactate or glutamine used at their relevant concentrations in culture media (Supplementary Figure 6B), explaining why others in non-metabolically controlled systems failed to detect MCT1-dependent migration other than random. 37 On another hand, CD147 upregulation under glucose starvation could help survivor cells to combat excess oxidative stress before evading to better soils: in malignant melanoma cells, silencing CD147 has been shown to induce ROS production. 38 Our characterization of the molecular pathway through which mitochondria control MCT1 and CD147 revealed a key role of mitochondrial ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The "Warburg effect" has been related to overexpression of hexokinase 2 (HX2) and its binding to mitochondria (Ko et al 2001;Geschwind et al 2002;Mathupala et al 2009;Pedersen 1978;Pedersen 2007). It also involves the monocarboxylate transporters MCT1 & MCT4 and the mitochondrial phosphate carrier (PIC) (Mathupala et al 2010;Izumi et al 2011;Mathupala et al 2006). However, how 3-BP selectively affects only cancer cells is not understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that most cancer cell lines express MCT1 rather than GLUTs. Eleven human lung cancer cells examined largely expressed MCT1 and MCT2, and a knockdown of these MCTs significantly reduced the migration of cancer cells (18). Our preliminary examination of human cancer also indicated that most cancers express MCT1 rather than GLUT1.…”
Section: Discussionmentioning
confidence: 86%